Hubungan Motivasi Dan Lingkungan Kerja Dengan Kinerja Perawat Di Rumah Sakit - Fajar Amanah Ariga; Lilis Pujiati (Jurnal Keperawatan Dan Kesehatan Holistik, 2026)
Optimal nurse performance can be achieved through high work motivation and a supportive work environment, both of which play essential roles in facilitating the implementation of nursing duties and contribute significantly to the successful delivery of nursing care by staff nurses. This study aimed to determine the relationship between work motivation, work environment, and the performance of staff nurses in the inpatient wards of Sundari General Hospital, Medan. This study employed an analytical observational design with a cross-sectional approach. The sampling technique used was non-probability sampling through total sampling, involving 30 respondents. Data were collected using a structured questionnaire. The results showed that 22 respondents (73.3%) had high work motivation and good performance, while 16 respondents (53.3%) reported a good work environment and demonstrated good performance. The results of the Chi-square test indicated a significant relationship between work motivation and work environment with the performance of staff nurses in the inpatient wards of Sundari General Hospital, Medan. Therefore, improving nurses' performance requires both strong work motivation and a supportive work environment.